ISSUES OF STRENGTHENING THE REPRODUCTIVE HEALTH OF THE POPULATION - Meliboyev Tavakkal Turgunovich (Galaxy International Interdisciplinary Research Journal, 2023)
The word "reproductive" comes from the Latin word "re-revival", "to repeat", produco-to create. In reproductive biology, it means reproduction of similar organisms . Reproductive health, that is, when and under what conditions a woman becomes a mother, information on creating optimal conditions for the health of both the mother and the unborn child will be covered .